The role of dual-energy computed tomography in the assessment of pulmonary function - Hwang, Hye Jeon; Kauczor, Hans-Ulrich (European journal of radiology, 2017)
The assessment of pulmonary function, including ventilation and perfusion status, is important in addition to the evaluation of structural changes of the lung parenchyma in various pulmonary diseases. The dual-energy computed tomography (DECT) technique can provide the pulmonary functional information and high resolution anatomic information simultaneously. The application of DECT for the evaluation of pulmonary function has been investigated in various pulmonary diseases, such as pulmonary embolism, asthma and chronic obstructive lung disease and so on. In this review article, we will present principles and technical aspects of DECT, along with clinical applications for the assessment pulmonary function in various lung diseases.
Available online 8 November 2016
Gesehen am 10.10.2018